2000
DOI: 10.1002/1096-9861(20001225)428:4<577::aid-cne1>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical localization of ionotropic glutamate receptors subunits in the adult quail forebrain

Abstract: The excitatory amino acid glutamate is implicated in the central control of many neuroendocrine and behavioral processes. The ionotropic glutamate receptors are usually divided into the N-methyl-D-aspartate (NMDA) and non-NMDA (kainate and AMPA) subtypes. Subunits of these receptors have been cloned in a few mammalian species. Information available in birds is more limited. In quail, we recently demonstrated that glutamate agonists (kainate, AMPA, and NMDA) rapidly (within minutes) and reversibly decrease in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
11
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 91 publications
(137 reference statements)
4
11
0
Order By: Relevance
“…In this paper, we therefore wanted to investigate whether the rapid changes in AA observed after copulation are mediated by endogenous glutamate release. This hypothesis was supported by the following lines of evidence: (1) glutamate receptors are expressed in regions of the avian brain containing aromatase cells (Cornil et al, 2000 ; Saldanha et al, 2004), (2) quail preoptic aromatase cells are sensitive to AMPA, kainate and NMDA in vitro (Cornil et al, 2004), (3) glutamate is released in rat medial preoptic area (MPOA) during sexual behavior (Dominguez et al, 2006) and (4) one study in zebra finches demonstrated that infusion of glutamate in an auditory telencephalic region containing aromatase leads to a transient decrease of estradiol concentration (Remage-Healey et al, 2008). …”
Section: Introductionmentioning
confidence: 87%
“…In this paper, we therefore wanted to investigate whether the rapid changes in AA observed after copulation are mediated by endogenous glutamate release. This hypothesis was supported by the following lines of evidence: (1) glutamate receptors are expressed in regions of the avian brain containing aromatase cells (Cornil et al, 2000 ; Saldanha et al, 2004), (2) quail preoptic aromatase cells are sensitive to AMPA, kainate and NMDA in vitro (Cornil et al, 2004), (3) glutamate is released in rat medial preoptic area (MPOA) during sexual behavior (Dominguez et al, 2006) and (4) one study in zebra finches demonstrated that infusion of glutamate in an auditory telencephalic region containing aromatase leads to a transient decrease of estradiol concentration (Remage-Healey et al, 2008). …”
Section: Introductionmentioning
confidence: 87%
“…These changes in aromatase activity can be induced by the activation of glutamate or dopamine receptors (Balthazart, Baillien, and Ball, 2002;Balthazart et al, 2003). Since glutamate and dopamine inputs and receptors are present in the preoptic area (Absil, Das, Ball, Casto, and Balthazart, 1992;Bailhache and Balthazart, 1993;Ball, Casto, and Balthazart, 1995;Balthazart and Absil, 1997;Cornil, Foidart, Minet, and Balthazart, 2000) and these receptors are expressed at the surface of aromatase cells themselves (Cornil, Seutin, Motte, and Balthazart, 2004c), it is therefore likely that afferent inputs related to a variety of environmental changes are able to rapidly affect estrogen production in the preoptic area.…”
Section: Site and Mechanisms Of Rapid Action Of Estrogensmentioning
confidence: 99%
“…The primary antibody concentrations were: GluR1 [1:100], GluR2/3 [1:250], and GluR4 [1:100]. According to manufacturer information and published studies, the immunogens for the GluR1, GluR2/3 and GluR 4 antisera show ≥85% homology to the corresponding avian sequences [6,22]. Western blot analysis in mammals and diverse avian species has shown these antisera selectively detect proteins of the predicted size for each GluR subunit [4,6,20,25,30].…”
mentioning
confidence: 99%
“…According to manufacturer information and published studies, the immunogens for the GluR1, GluR2/3 and GluR 4 antisera show ≥85% homology to the corresponding avian sequences [6,22]. Western blot analysis in mammals and diverse avian species has shown these antisera selectively detect proteins of the predicted size for each GluR subunit [4,6,20,25,30]. Moreover, blocked controls show the specificity of these antisera in mammals and birds [21], and in the case of GluR2/3 specificity is supported by the concordance in distribution between immunolabeling and GluR2 in situ hybridization [27].…”
mentioning
confidence: 99%
See 1 more Smart Citation